2018
DOI: 10.1002/jclp.22642
|View full text |Cite
|
Sign up to set email alerts
|

Developing self‐regulation in a dysregulating world: Attachment and Biobehavioral Catch‐up for a toddler in foster care

Abstract: Toddlers in foster care have typically experienced histories of maltreatment and disruptions in relationships with primary caregivers. As a result, they are at increased risk for developing disorganized attachment and showing emotional, behavioral, and physiological dysregulation. Attachment and Biobehavioral Catch-up for Toddlers in Foster Care (ABC-T) was developed to address the needs of these vulnerable children by supporting foster parents in responding with nurturance to children's distress, following ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Three main parenting targets are addressed during the intervention, namely nurturing the child when distressed, following the child’s lead (synchronous behavior), and behaving in nonfrightening ways ( Dozier and Bernard, 2017 ). In ABC-T for toddlers the third target is replaced by helping the caregivers to serve as co-regulators when toddlers show signs of dysregulation as, e.g., anger or frustration or aggressive behavior ( Lind et al, 2017 ; Imrisek et al, 2018 ). It could be shown that the ABC intervention led to enhanced caregivers’ synchronous behaviors and improved attachment behavior, cortisol production, and executive functioning in the child ( Dozier et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three main parenting targets are addressed during the intervention, namely nurturing the child when distressed, following the child’s lead (synchronous behavior), and behaving in nonfrightening ways ( Dozier and Bernard, 2017 ). In ABC-T for toddlers the third target is replaced by helping the caregivers to serve as co-regulators when toddlers show signs of dysregulation as, e.g., anger or frustration or aggressive behavior ( Lind et al, 2017 ; Imrisek et al, 2018 ). It could be shown that the ABC intervention led to enhanced caregivers’ synchronous behaviors and improved attachment behavior, cortisol production, and executive functioning in the child ( Dozier et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three main parenting targets are addressed during the intervention, namely nurturing the child when distressed, following the child's lead (synchronous behavior), and behaving in nonfrightening ways (Dozier and Bernard, 2017). In ABC-T for toddlers the third target is replaced by helping the caregivers to serve as coregulators when toddlers show signs of dysregulation as e.g., anger or frustration or aggressive behavior (Lind et al, 2017;Imrisek et al, 2018). It could be shown that the ABC intervention led to enhanced caregivers' synchronous behaviors and improved attachment behavior, cortisol production, and executive functioning in the child (Dozier et al, 2013).…”
Section: Reactive Attachment Disorder (Rad)mentioning
confidence: 99%
“…Throughout the 10‐week intervention, coaches provide “in the moment” comments to highlight examples of responsive caregiving, connect parent behaviors with intervention targets and child outcomes, and suggest appropriate parent responses to child behaviors (Dozier et al, 2018; Hoye, and Dozier, 2018). Although originally developed for infants in foster care, more recent adaptations of ABC target neglected children who are not in foster care, international adoptees, toddlers in foster care, and neglected toddlers (Dozier et al, 2018; Imrisek et al, 2018).…”
Section: Interventions To Address Behavioral and Neurobiological Funcmentioning
confidence: 99%